2008
DOI: 10.1037/0012-1649.44.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Task experience and children's working memory performance: A perspective from recall timing.

Abstract: Working memory is an important theoretical construct among children, and measures of its capacity predict a range of cognitive skills and abilities. Data from 9- and 11-year-old children illustrate how a chronometric analysis of recall can complement and elaborate recall accuracy in advancing our understanding of working memory. A reading span task was completed by 130 children, 75 of whom were tested on 2 occasions, with sequence length either increasing or decreasing during test administration. Substantial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Methodologically, previous research has shown that children often do not progress beyond correct recall of more than three item-sequences in reading span (e.g. Towse, Cowan, Horton & Whytock, 2008). Therefore, to facilitate task administration, we presented children with two-item and three-item memory sequences, rather than attempting to identify span length for each child.…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, previous research has shown that children often do not progress beyond correct recall of more than three item-sequences in reading span (e.g. Towse, Cowan, Horton & Whytock, 2008). Therefore, to facilitate task administration, we presented children with two-item and three-item memory sequences, rather than attempting to identify span length for each child.…”
Section: Discussionmentioning
confidence: 99%
“…Scores were based on the total number of words correctly recalled, with higher scores indicating better working memory. This method of scoring has good reliability in adults and children [20,21].…”
Section: Cognitionmentioning
confidence: 97%
“…Preschoolers are able to form thematic representations of events and report on them, based on their more central components (Nelson, 1996). Thematic information also influences word recall tasks, not only in children aged 7-11 (e.g., Towse, Cowan, Horton, & Whytock, 2008) but also into adolescence and adulthood (e.g., Belacchi et al, 2013).…”
Section: Semantic Representationsmentioning
confidence: 99%